Smoother and stronger high speed sintered elastomers through surface modification process. (2017) - Norazman, Farhana; Smith, Patrick; Ellis, Adam; Hopkinson, Neil
High speed sintering is a novel additive manufacturing process which creates parts by employing a combination of inkjet printing and infrared heating to sinter successive layers of polymer powder. This paper investigates the effect of a new surface modification method called the PUSh process on the mechanical properties of high speed sintered elastomer. ALM TPE210-S elastomeric powder was used to manufacture specimens, and the PUSh process was subsequently performed on selected specimens. Surface roughness and mechanical properties of TPE210-S specimens were measured. The results show that the PUSh process reduced surface roughness by 50% from 20 to 10 µm. Finished specimens had 50% higher values of ultimate tensile strength, Young's modulus and elongation at break compared to unfinished specimens, and tear strength was significantly improved by 233%. The process resulted in 3% average part shrinkage while part hardness remains unchanged. Overall, the mechanical properties of high speed sintered TPE210-S elastomer were improved by the PUSh process.